Local Heroes Enter History Class - Kurniawan, Ganda Febri; Warto, Warto; Sutimin, Leo Agung (Indonesian Journal of History Education, 2021)
This study aims to critique the textual narrative of heroic history, with a particular focus on the philosophy of the Local Hero, the integration of Local Heroes into history classes, and the academic community's reception of the Local Hero concept. Employing a qualitative approach with a critical ethnographic design, the research reveals several key findings: 1) The Local Hero concept is philosophically well-suited for teaching local history; 2) History classes become more engaging when popular concepts are incorporated, especially given that the millennial generation tends to be less interested in overly political or elitist historical narratives, making the Local Hero concept particularly relevant; and 3) The concept receives positive feedback from both educators and students in the classroom. Based on these findings, the researcher concludes that there is a current need for innovation in history teaching to align with contemporary values and interests.